City of ashes : the Shadowhunter Chronicles - Clare, Cassandra (The mortal instruments, 2015)
Love and power are the deadliest temptation... Haunted by her past, Clary is draggled deeper into New York City's terrifying underworld of demons and Shadowhunters - but can she control her feelings for a boy who can never be hers?